2018
DOI: 10.1155/2018/3729402
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PGRN Levels Are Increased but Not Associated with Insulin Sensitivity or β-Cell Function in Chinese Obese Children

Abstract: Progranulin (PGRN), a novel peptide that has recently emerged as an important regulatory adipokine, is relevant to energy homeostasis and obesity in animals and adult humans. Little is known about its roles in children. The aim of the current study was to determine the potential role of PGRN and explore its relationship to various obesity-related markers in obese children. This was a cross-sectional study composed of 77 children (43 obese and 34 healthy, age 8.68 ± 0.28 and 8.46 ± 0.45 years, resp.). The PGRN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…One of the hypotheses suggests that obesity may represent a state of chronic oxidative stress and low-grade inflammation. 7,14 The results are in agreement with the previous studies, we also found that the level of hsCRP in obesity participants were significantly higher than nonobesity group, 15,16 and vitamins may reduce the risk of obesity by…”
Section: Discussionsupporting
confidence: 92%
“…One of the hypotheses suggests that obesity may represent a state of chronic oxidative stress and low-grade inflammation. 7,14 The results are in agreement with the previous studies, we also found that the level of hsCRP in obesity participants were significantly higher than nonobesity group, 15,16 and vitamins may reduce the risk of obesity by…”
Section: Discussionsupporting
confidence: 92%
“…A 180-min OGTT (1.75 g/kg glucose, maximum 75 g) according to the American Diabetes Association criteria was performed in all obese subjects 17. Venous blood samples were obtained by venipuncture after overnight fasting at 0, 30, 60, 120 and 180 mins to measure serum glucose, insulin and CTRP3 levels as described previously 19…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of human studies have demonstrated the possible role of PGRN in insulin resistance and obesity, but data are highly controversial. Generally, hyperprogranulinemia has been reported to be linked to adiposity, metabolic parameters, insulin resistance and inflammatory markers both in adult [ 63 ] and childhood obesity [ 64 ]; however, in other studies PGRN has not been found to be associated with insulin sensitivity and beta-cell function [ 65 ]. In obese healthy men, significantly improved body composition and insulin resistance and decreased serum PGRN levels were detected after 8-week circuit resistance training [ 66 ].…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%